Assessment of life quality and health perception among recovered COVID-19 patients: multivariate analysis - own material and a review of previous reports on life quality assessment among convalescents - Natalia Zięba; Grażyna Stryjewska-Makuch; Karolina Goroszkiewicz; Maciej Zieliński; Adam Dadok; Barbara Pietrzyk; Julia Gajewska; Katarzyna Miśkiewicz-Orczyk; Grażyna Lisowska (Nofer Institute of Occupational Medicine, 2022)
Background The SARS-CoV-2 virus, causing acute respiratory disease, is responsible for the COVID-19 pandemic, which began in early 2020. In addition to symptoms typical of respiratory tract infections, the virus causes a number of non-specific, often long-lasting effects that hinder the daily functioning of individuals. The aim of the study was a subjective assessment of life quality and health perception among recovered COVID-19 patients. Material and Methods The study included 337 subjects who had been infected with SARS-CoV-2 confirmed by a positive RT-PCR test. The study participants were of legal age. The convalescents completed a questionnaire that contained 26 questions about gender, height, body weight, blood type, general and specific symptoms, comorbidities, hospital stay and duration of specific symptoms, the severity of which was assessed on the Visual Analogue Scale (VAS). The subjects determined whether the COVID-19 infection influenced their health perception and life quality. Results According to 46% of the respondents, COVID-19 had an impact on their quality of life and health. The chance for patients to notice the negative effects of COVID-19 on their current health status and life quality increased with each subsequent symptom of the disease by 49%, with each day of its occurrence by 3%, and with each VAS point of the severity of all infection symptoms by 30%. Conclusions The study shows that COVID-19 disease affects life quality and overall health perception after recovery. Significant impact of COVID-19 on the quality of life should be a signal to create mental support and rehabilitation programs for convalescents to minimize discomfort and shorten the duration of absenteeism from work. Med Pr. 2022;73(6):449-56